Digital nations -- smart cities, innovation, and sustainability : 16th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2017, Delhi, India, November 21-23, 2017, Proceedings /: 16th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2017, Delhi, India, November 21-23, 2017, Proceedings. (2017) - Unknown
No abstract available